Sosialisasi Pembuatan Pestisida Nabati Bawang Putih (Allium sativum) Sebagai Upaya Menciptakan Desa Peduli Lingkungan Darat - Alfa Dirsista Damayanti; Afiyah Dwi Salma; Hasna Aqilah Putri Agdy; Riskita Dinda Mulia; Sylvi Intan Maylina; Doddy Agus Prakoso; Fitrianti Rahmawati; Aulia Niken Dhea Prameswari; Tukiman Tukiman (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Pesticides are all chemicals and other materials as well as microbes and viruses that are used to eradicate or prevent pests and diseases that damage plants. The majority of farmers use chemical pesticides because they are easy to apply practically, fast reaction, and more efficient. Vegetable pesticides or biopesticides are solutions of organic insecticide compounds that function as plant pest control and are environmentally friendly because the active ingredients are easily decomposed in nature. Compiled from the Village Information System page, it is known that the SDGs score of Lebo Village, the point of the village caring for the land environment, is at a percentage of 33.33%, which indicates that the aspect of caring for the land environment in Lebo Village is still low. Based on these conditions, students try to help improve village development in the aspect of land environmental care. The vegetable pesticide socialization activity is one of the activities of the KKN-T Bela Negara of UPN 'Veteran' East Java Students. The socialization was held on Saturday, July 27, 2024. The target of this vegetable pesticide socialization was attended by 18 PKK RW 05 women in Lebo Village, Sidoarjo, consisting of 3 RTs, namely RT 16, 17, and 18.